2022
DOI: 10.3390/healthcare10061108
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Teleorthodontics in Orthodontic Emergencies during the COVID-19 Pandemic: A Systematic Review

Abstract: Background. Coronavirus disease has subjected the whole of humanity to two years of social isolation and a series of restrictions. These circumstances have led to the use of information technology in an increasingly widespread manner. Even in the dental field, telematic means have been used to respond to emergencies. The aim of this systematic review of the literature is to evaluate the types of orthodontic emergency that occurred most often and how they were managed by teleorthodontics during the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The ability to triage remotely to determine whether a patient needs an office visit or if there is a chance to resolve the issue through the media,[ 17 18 ] the ability to cut down on the amount of time the patient spends in the chair,[ 26 ] and the ability to send and evaluate images and radiographs quickly[ 10 19 ] are a few of these benefits. The ability to reassure patients who experience anxiety, fear, or a sense of abandonment during therapy,[ 19 26 27 ] as well as the potential for periodically checking on patients’ oral health status and encouraging them to practice good oral hygiene,[ 26 27 ] are additional positive aspects that should be highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to triage remotely to determine whether a patient needs an office visit or if there is a chance to resolve the issue through the media,[ 17 18 ] the ability to cut down on the amount of time the patient spends in the chair,[ 26 ] and the ability to send and evaluate images and radiographs quickly[ 10 19 ] are a few of these benefits. The ability to reassure patients who experience anxiety, fear, or a sense of abandonment during therapy,[ 19 26 27 ] as well as the potential for periodically checking on patients’ oral health status and encouraging them to practice good oral hygiene,[ 26 27 ] are additional positive aspects that should be highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it doesn’t appear to be appropriate in every circumstance or for extended periods of time, Saccomanno et al . [ 27 ] in their study from 2020 believe that using teledentistry is a good answer. Clinicians demonstrated that the use of teleorthodontics could merely manage functional appliances and aligners, requiring just follow-up to continue therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the screening of titles and abstracts, 171 full-text articles were obtained and evaluated for the preset eligibility criteria. During the full-text screening process, we excluded reviews in which we were unable to judge whether the review met the eligibility criteria due to lacking key information, i.e., important details on the design, intervention or if the outcome measures of the included studies were not clear or missing [9,[22][23][24][25][26][27][28][29]. One review's conclusion about the costs was in contrast with the conclusion stated in the original article and was therefore excluded during the data-selection process [30].…”
Section: Resultsmentioning
confidence: 99%
“…Various companies have spent the last decade gathering big data regarding teeth movement resulting from aligner treatments, which have provided them with an essential foundation for advanced AI implementations supporting effective teeth movement. However, other major aspects of orthodontics—patient communication, coaching, and no less important, clinician control over treatment progress, have become a new domain for AI implementations [ 49 , 91 , 92 , 93 , 94 , 95 , 96 ]. Many of these implementations were introduced as telehealth solutions, benefiting from the interpersonal contact restrictions of the COVID19 pandemic.…”
Section: Resultsmentioning
confidence: 99%